The Role of Parents in Improving Children's Learning Motivation in Arabic Language Learning - Binti Rosyidah; Annisa Nurwinda Sari (STAI Miftahul Ula Nganjuk, 2020)
This study discusses the role of parents in highlighting children's learning motivation in grade II-A Arabic language learning at MI Kunuzun Naja Wonotengah. The reason researchers discussed this problem was because of the lack of parental control at home towards children's learning activities. In fact, parents are assets that play a big and important role in improving children's knowledge. The interests, talents, abilities, and potentials of children as learners will not develop optimally without the help of parents. This type of research is qualitative. The study was conducted in grade II-A with subjects of 6 students and 6 parents. Without motivation one's efforts will not be able to achieve good results, as well as in terms of learning. Learning will be better if it is always accompanied by motivation. Methods used by parents in motivating children in research in the form of: (1) Gift giving (2) Giving praise and (3) Sanctions (punishment). This study aims: (1) To find out the parents in improving children's learning motivation in grade II-A Arabic language learning at MI Kunuzun Naja Wonotengah Purwoasri. (2) To know the method of parents in providing motivation to their children. The results of this study are showing the role of parents in improving their child's learning motivation and what methods are used to increase their child's motivation.